ASSESSMENT OF FUNGAL DISEASES OF STORED MAIZE (Zea mays L.) IN SOME WAREHOUSES IN LOKOJA, KOGI STATE - Audu, Nasir O.; Musa, Musa A.; Adams, Abiodun E.; Zakari, Adeiza D.; Sanni, Anataku M. (FUDMA Journal of Sciences, 2025)
Maize (Zea mays) is a vital cereal crop for food security in Nigeria, yet postharvest losses due to fungal contamination during storage remain a significant challenge. This study assessed fungal pathogens affecting stored maize in warehouses across three locations (Mami, Lokongoma, and Kpatar) in Lokoja Kogi State Nigeria. Infected maize samples were collected, and fungi were isolated using Potato Dextrose Agar media, followed by morphological identification via microscopy. Four fungal species were identified: Aspergillus fumigatus, Fusarium oxysporium, Mucor hiemalis and Candida albicans. Frequency analysis revealed Aspergillus spp. as the most prevalent (37.87%), followed by Candida sp. and Mucor spp (25.25% each), with Fusarium spp being the least frequent (12.6%). The high prevalence of Aspergillus spp. aligns with studies from similar agro-ecological zones, though discrepancies in species distribution compared to other regions highlight the influence of local environmental factors such as humidity, temperature and storage practices. Mycotoxin-producing fungi, particularly Aspergillus and Fusarium, pose significant health risks, including carcinogenic effects, emphasizing the urgency of addressing contamination. The study underscores suboptimal storage conditions such as inadequate drying, poor ventilation, and lack of pest control as key drivers of fungal proliferation. Recommendations include adopting improved preservation techniques, such as hermetic storage, regular mycotoxin monitoring, and enhancing warehouse infrastructure to regulate temperature and humidity farmer’s education on postharvest management is critical to mitigating economic losses and safeguarding public health. This research provides actionable insights for reducing fungal contamination in maize storage systems, contributing to food safety and sustainability in Nigeria and similar tropical regions.